Comparative study on effect of pH on pure nickel oxide and copper oxide nanoparticles using sodium hydroxide precursor photocatalytic activity - Ravichandran, Aiswarya; Kumar, Ashok Kumar; Chandrasekar, Amirthavarshini; Chinnathambi, Udhayakeerthana; Thirunavukarasu, Kalaivani (AIP conference proceedings, 2024)
Photocatalysis is a recently developed technique that may be used as a supplement or alternative to the current drinking water treatment procedure. Applications for photocatalysts include the treatment of wastewater, antifogging, sterilization, deodorization, antifouling, air purification, conservation and energy storage. The photocatalytic elimination of trace hazardous organic compounds in air and water has been the subject of several investigations; nonetheless, there are still certain concerns about their practical application. Nickel oxide (NiO) and Copper oxide (CuO) nanostructure has been prepared. Nanoparticles are essential to develop a wide range of impact industrial product. The characterization studies such as X-ray Diffraction (XRD), UV-Visible (UV-Vis), Fourier Transform Infrared (FTIR), Raman Spectroscopy and Scanning Electron Microscope (SEM) are used. It can be shown that the produced nanoparticles have significant photocatalytic activity in addition to having a great dispersion in dye solution.